The case of a patient of 80 years old with epilepsy and neurocognitive disorders - Eliza Oleksy; Paulina Kasperska; Remigiusz Sokołowski; Anna Ziółkowska; Karolina Klimkiewicz-Wszelaki; Walery Zukow; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Background. Epilepsy is a very widespread disease in the world. It is one of the most common neurological diseases of old age. However, older age is also associated with multi-morbidity and cognitive decline. This will result in a decrease or loss of the possibility of being independent of other people in the scope of basic everyday activities such as: moving, nutrition, sphincter control and maintaining personal hygiene. Disorders occurring in such a wide range in people with dementia often translate into disability in everyday life. Improving the quality of life of patients consists primarily in maintaining autonomy in self-service for as long as possible. Therefore, one of the most important elements of improving the quality of life of an elderly person is the early detection of neurocognitive disorders, rehabilitation of the patient and performing prescribed screening tests. Case report. A 80- year-old patient admitted to the Clinic of Geriatric in urgent matter due to dizziness and falls. Patient living with family, dependent in daily life, financially self-sustaining. Patient takes medicines from different groups due to multiple diseases. Patient's symptoms: dizziness and frequent falls. Because of the last complain, consulted in the department of emergency medicine, head tomography was conducted. The test showed no signs of fresh bleeding. The patient suffers from epilepsy. Patient has condition after treatment of subdural hematoma, in the state after heart attacks in 2001, 2003, 2004. In 2003 coronary angioplasty was performed. Patient is also suffering from hypertension, type 2 diabetes and chronic kidney disease. No use of drugs, alcohol and cigarettes. Result. The risk of functional limitations increases with the number of diseases present and is particularly large in people over 80 years of age. Multiple diseases is a serious problem in rehabilitation, therefore geriatric rehabilitation should be carried out on many levels. A comprehensive geriatric assessment helps diagnose the problem and develop a plan to improve the patient's quality of life. In addition, vitamin supplementation should be implemented in the elderly. Also medications used by the elderly and behavioral changes should be controlled. Patients should follow the recommendations of health care workers and attend both laboratory and neuropsychological monitoring tests.